Aksesibilitas Pendidikan Gratis Bagi Masyarakat Miskin di MA Nurul Ali Secang - Fina Umu Rif Athi; Sabarudin Sabarudin; Titis Rosowulan (Jurnal Ilmiah Wahana Pendidikan, 2023)
Poor people who wish to continue their studies at the senior high school level can choose MA Nurul Ali Secang as a place to educate their children. MA Nurul Ali Secang is a boarding school-based private school. The purpose of this study was to examine information regarding the accessibility of education for the poor at MA Nurul Ali Secang. The research method used is a qualitative method with a descriptive approach. Data collection techniques are interviews and literature study. The location or object of this study is at MA Nurul Ali which is located in a rural area. The research location is at MA Nurul Ali. The time of the research was in November 2022. The research results obtained were that the poor could get access to free education by fulfilling 3 conditions, namely having KIP, PKH or being orphans. Free education is very much needed to accommodate the poor so that high dropout rates do not occur.